Experimental/modelling study of residual stress in Al/SiCp bent bars by synchrotron XRD and slitting eigenstrain methods - Song, X; Chardonnet, S; Savini, G; Vorster, W; Korsunsky, A (Trans Tech Publications, 2008)
The aim of this study presented here was to evaluate the residual stresses present in a bar of aluminium alloy 2124-Tl matrix composite (MMC) reinforced with 25vol% particulate silicon carbide (SiCp) using X-ray diffraction and 3D profilometry (curvature measurement using Mitutoyo/Renishaw coordinate measurement machine) and comparing these results with numerical models of residual strain and stress profiles obtained by a simple inelastic bending model and Finite Element Analysis (FEA). The residual strain distribution was introduced into the test piece by plastic deformation in the 4-point bending configuration. At the first stage of this study the elastic-plastic behaviour of the MMC was characterized under static and cyclic loading to obtain the material parameters, hardening properties and cyclic hysteresis loops. Subsequently, synchrotron X-ray diffraction and CMM curvature measurements were performed to deduce the residual stress profile in the central section of the bar. The experimental data obtained from these measurements were used in the inelastic bending and FEA simulations. The specimens were then subjected to incremental slitting using EDM (electri discharge machining) with continous back and front face strain gauge monitoring. The X-ray diffraction and incremental slitting results were then analysed using direct and inverse eigenstrain methods. Residual stresses plots obtained by different methods show good agreement with each other.